The Role of Religious Social Activities in Instilling Islamic Educational Values in Rural Communities: A Study of Banaran Hamlet - Ayu, Yamita; Umar, Muallief; Fathurrohman, Amang; Syawaludin, Makhfud; Mukaromah, Ning (IERA, Islamic Education and Research Academy, 2024)
This study explores how Islamic educational values are instilled through religious social activities in Banaran Hamlet, Muneng Village, Kediri Regency, focusing on the strategies employed, the values taught, and the forms of activities used. Using a qualitative approach with semi-structured interviews, participant observations, and document analysis involving 15 key informants, the study found that activities such as tahlilan, yasinan, ndiba’, and mosque-based recitations effectively promote values of worship, morality, solidarity, and piety. Strategies such as socialization, habituation, and role modeling by religious leaders and community elders were identified as key in transmitting these values. Additionally, the integration of local cultural practices with Islamic teachings enhanced the accessibility and relevance of the values taught. This research highlights the potential of community-based religious social activities as informal educational tools in rural areas, contributing to the broader understanding of how such practices can foster moral and spiritual development, especially in communities with limited access to formal education